A methodology to qualitatively select upcycled building materials from urban and industrial waste - Parece, S. (2022)
The rising concern about climate change and other challenges faced by the planet led society to look for different design solutions and approaches towards a more balanced relationship between the built and natural environment. The circular economy is an effective alternative to the linear economic model inspired by natural metabolisms and the circular use of resources. This research explores how innovative strategies can be integrated for evaluating local urban and industrial wastes into sustainable building materials. A literature review is conducted focusing on circular design strategies, re-use, recycle, and waste transformation processes. Then, a methodology for the selection of upcycled and re-used building materials is developed based on Ashby’s method. A total of thirty-five types of partition walls, which include plastic, wood, paper, steel, aluminium, and agricultural wastes, are evaluated using a multi-criteria decision aid (M-MACBETH). Among these solutions, ten types of walls show high-performance thermal and sound isolation, fourteen types are effective for coating, and two exhibit structural reliability. Regardless of their functional limitations, the proposed solutions based on waste materials bear great potential within the construction industry.